The Huberto Rohden trajectory: a sketch of a biography: The journey of Huberto Rohden: sketch of a biography (Revista de História da UEG (REVHIST), 2025)
This paper aims an initial biography about Huberto Rohden, active intellectual around most of the 20th century. Born in São Ludgero, Santa Catarina state in Brazil, Rohden develop first his way as a priest from Catholic Church, but in the year of 1945 he formally disengagement himself from the Church. This is the beginning of Rohden trajectory as an intellectual, firstly as professor in American University in Washington, USA, a then as a speaker by hers self-realization center Alvorada. His extensive trajectory induct us to understand the development of publishing market in Brazil, since Rohden published an intensive quantity of books by several publishers, until he starts his own publisher the Alvorada in 1970s. His pupil Martin Claret continues to publish the Rohden work, changing the publisher name to his own around 1990s and acting in the market until today. Correlating Rohden individual trajectory with the historical context he is in, get us to understand the religious and spiritual thinking and the publish industry in Brazil around the 20th century. Mostly where consulted archives from São Ludgero, Florianopolis, Hemeroteca Digital da Bibliotheca Nacional and the IPHAE (Instituto do Patrimônio Histórico e Artístico do Estado do Rio Grande do Sul).Keywords: Huberto Rohden. Religiosity. Publishers market. Intellectuals.
Keywords: Huberto Rohden; Religiosity; publishers market; intellectuals